Experimental Study of PVTx Properties of Mixture Refrigerant R1234yf/R134a - Chen Rishuai; Qi Yingxia; Wu Dong (Zhileng xuebao)
In order to get the thermophysical properties of mixed refrigerants R1234yf/R134a, the PVT properties of mixture refrigerant R1234yf/R134a with mass fraction 55%/45%, 50%/50%,45%/55% in the range of 268 ~ 323 K were measured by using high-precision PVTx apparatus which is based on the Burnett method.The gas virial equation of these mixed refrigerants was fitted based on the measured data. It turned out that the experimental data agreed well with the equations.